PRODUKTIVITAS CRUSHER DALAM PENGOLAHAN ANDESIT PT. BUMI KEJAYAN, DUSUN DAMPOL, DESA BENERWOJO, KECAMATAN KEJAYAN, KABUPATEN PASURUAN, PROVINSI JAWA TIMUR - Berek, Novrinus Leonardo; Cahyono, Yudho Dwi Galih; Bahar, Hendra (Institut Teknologi Adhi Tama Surabaya, 2024)
PT Bumi Kejayan, located in Dampol Hamlet, Benerwojo Village, Kejayan District, Pasuruan Regency, East Java Province, has an IUP (Mining Business License) area of 42.54 Ha. Efficiency in crusher production needs to be done in order to reduce work resistance time and increase production in achieving the target. This study aims to determine the production capacity of the crusher plant, the obstacles that occur in production activities and make efforts to reduce the time of work obstacles and increase production targets. In this study, the research method was carried out by calculating the production of crushers, hoppers, conveyor belts, vibrating screens and tool availability from the time of work resistance. The calculation results obtained are jaw crusher production of 10,810 tons / month, while the availability of tools in one working month MA (Mechanical Availability) 96.17%, UA (Use of Availability) 94.97%, and EU (Effective Utilization) 91.57%. After improving the performance of the crusher and reducing the working time constraints, the actuary crusher production increased to 12,171 tons/month while the availability of tools also increased with MA (Mechanical Availability) 99.27%, UA (Use of Availability) 99.27%, and EU (Effective Utilization) 98.55%, so that the fulfillment of the production target of 12,000 tons/month was achieved.